Gerakan Desa Peduli Sampah: Membangun Kesadaran Bersih Lingkungan Desa Wanasari Kecamatan Muara Wahau - Hartono Hartono; Achmad Fahruddin; Ajis Supangat; Muchammad Abdul Basir (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2026)
This community service program aimed to enhance community awareness and participation in maintaining environmental cleanliness through the Village Waste Awareness Movement. The program employed a Participatory Action Research (PAR) approach, involving community members in problem identification, action implementation, community participation, evaluation, and reflection processes. The activities included waste management socialization, education on organic and inorganic waste segregation, community clean-up campaigns, discussions on village-level waste management solutions, and environmental awareness education for children and adolescents. The results indicated improved community understanding of proper waste management, increased participation in environmental cleanliness activities, and the development of collective awareness that environmental cleanliness is a shared responsibility. Furthermore, the program strengthened community cooperation and social capital in supporting environmental sustainability. Although challenges remain, including limited waste management facilities and the need for continuous assistance, the findings demonstrate that a participatory approach is effective in fostering environmental awareness and behavioral change.